First principles studies for the interaction of hydrogen with a Li(100) surface - Arboleda, Nelson B., Jr. (Animo Repository, 2005)
We investigate the interaction of molecular/atomic hydrogen with the Li surface. We calculate the potential energy surfaces (PESs) for H2 and the potential energy curves (PECs) for H at symmetric sites on a Li(100) surface within the density functional theory. The PESs results show the dependence of the energy barriers for H2 dissociative adsorption and the stable adsorption sites for the dissociated H atoms on the H2 center-of-mass (CM) position and the H2 orientation relative to the surface. Also, reaction paths for the direct absorption of H2 can be seen when the H2 CM is directly above the bridge site of the Li(100) surface. Meanwhile, the PECs results indicate that the energy barriers for H absorption and the stable H adsorption sites depend on the H lateral position relative to the surface. A very low energy barrier was observed for H absorption on the bridge site of the surface. Finally, we present a practical explanation of the PESs' and PECs' dependence on the H2 position and orientation relative to the surface from the interaction between the electrons of hydrogen and of the substrate atoms, as well as from the lattice structure of the substrate. ©2005 The Physical Society of Japan.